Decision for Reinvestment in Capital Budget: Material and non Material Sanction as Antecedent - Yenni Agustina (Politeknik Negeri Lampung, 2011)
This research aims to test the influence of applying material and non material sanction toward of escalation of commitment. Hypothesis testing is done by using experimental with factorial between subject design 2x2. This research is done in Lampung University for students who have taken financial management lesson. They are 60 students. Based on the result of manipulation test that data is inserted into next processing. It is amount 56 people. Examination of hypothesizing is done by using one way anava statistical analysis, result of research indicates that result of this research as the same as the agency theory, that escalation of commitment is rational thing for a manager. It is supported by mean which is produced by group 3, that is 7133 when sanction of material in the form of loss of bonus which will be received by manager, so that the pressure push manager to take risk of failing activities. But, yielded influence is not significant statistically at mistake level 5%. It shows existence of other factors which influence interaction of two variables. Estimated factors are for example feeling responsible.Key words: sanction, eskalation of commitment, agensi theory, insentive theory